The Dynamic Impact of FX Interventions on Financial Markets - Menkhoff, Lukas; Rieth, Malte; Stöhr, Tobias (The Review of Economics and Statistics, 2021)
Abstract Evidence on the effectiveness of foreign exchange (FX) interventions is either limited to short horizons or hampered by debatable identification. We address these limitations by identifying a structural vector autoregressive model for the daily frequency with an external instrument. Generally we find, for freely floating currencies, that FX intervention shocks significantly affect exchange rates and that this impact persists for months. The signaling channel dominates the portfolio channel. Moreover, interest rates tend to fall in response to sales of the domestic currency, whereas stock prices of large (exporting) firms increase after devaluation of the domestic currency.